A Europe-wide assessment of antibiotic resistance rates in Bacteroides and Parabacteroides isolates from intestinal microbiota of healthy subjects. (April 2020) - Sóki, József; Wybo, Ingrid; Hajdú, Edit; Toprak, Nurver Ulger; Jeverica, Samo; Stingu, Catalina-Suzana; Tierney, Daniel; Perry, John David; Matuz, Mária; Urbán, Edit; Nagy, Elisabeth; ,
Abstract: Here, we sought to assess the levels of antibiotic resistance among intestinal Bacteroides and Parabacteroides strains collected between 2014 and 2016 in Europe and also attempted to compare resistance levels between clinical and commensal isolates. Bacteroides and Parabacteroides isolates were recovered from faecal samples via the novel Bacteroides Chromogenic Agar (BCA) method. Antibiotic susceptibilities were determined by agar dilution for ten antibiotics. The values obtained were then statistically evaluated. Altogether 202 Bacteroid es/ Parabacteroides isolates (of which 24, 11.9%, were B. fragilis ) were isolated from the faecal specimens of individuals taken from five European countries. The percentage values of isolates resistant to ampicillin, amoxicillin/clavulanate, cefoxitin, imipenem, clindamycin, moxifloxacin, metronidazole, tetracycline, tigecycline and chloramphenicol were 96.6, 4.5, 14.9, 2.0, 47.3, 11.4, 0, 66.2, 1.5 and 0%, respectively. These values are close to those reported in the previous European clinical Bacteroides antibiotic susceptibility survey except for amoxicillin/clavulanate and clindamycin, where the former was lower and the latter was higher in normal microbiota isolates. To account for these latter findings and to assess temporal effects we compared the data specific for Hungary for the same period (2014–2016), and we found differences in the resistance rates for cefoxitin, moxifloxacin and tetracycline. Highlights: BCA plates were successfully used for isolation of Bacteroides strains from stools. Antibiotic susceptibility values were roughly comparable that of clinical strains. But augmentin and clindamycin gave statistically significant differences. Time-paired data from Hungary differed for cefoxitin, moxifloxacin and teracycline We assumed that traits of clinical and stool strains are different in the intestine.